A new species of marine goby Trimma (Teleostei:Gobiidae) from Taiwan - Chen, I-Shiung; Harefa, Tonisman (Zootaxa, 2024)
A new species of marine goby, Trimma tigrinum sp. nov. is discovered and collected from the coastal waters off eastern and southern Taiwan. It can be well distinguished from other congeners by the following unique combination of features: (1) fin rays: D2 I/9, A I/9, P 17–19; second and third spines of D1 equal in length and not elongated; D2 rays branched; first ray of A not branched; fifth ray of V unbranched. (2) Squamation: LR 23–24 (modally 23), TR 6–7 (modally 7), PredS 7–8; no scales on the cheek and opercle. (3) Interorbital width narrow with deep trench and postorbital trench with slightly groove. (4) Specific colorations: cheek with two yellow vertical bands; anterior margin of pectoral-fin base with large yellow bar, two third of pupil diameter-sized; spine of second dorsal-fin with two small, dark reddish spots. dorsum from D1 to dorsal procurrent caudal-fin with seven yellow-orange bands like saddles; ventral from origin A to ventral procurrent caudal-fin with five diffuse yellowish or reddish orange bands. The molecular evidence from mtDNA COI sequence is also revealed that the new species is discrete species from others. A diagnostic key to nominal species of Trimma from Taiwanese waters would be also provided in this paper.